The - Hans J. Hillerbrand; editor in chief (Oxford University Press, 1996)
The Oxford Encyclopedia of the Reformation is the first major reference to cover the immense subject of the Reformation in its entirety. Setting the issues of theology and ecclesiology within the broader context of the social and intellectual history of the time, it is the most authoritative reference available on early modern European society as a whole